2011
DOI: 10.1175/2010jpo4557.1
|View full text |Cite
|
Sign up to set email alerts
|

Diapycnal Mixing in the Antarctic Circumpolar Current

Abstract: The vertical dispersion of a tracer released on a density surface near 1500-m depth in the Antarctic Circumpolar Current west of Drake Passage indicates that the diapycnal diffusivity, averaged over 1 yr and over tens of thousands of square kilometers, is (1.3 6 0.2) 3 10 25 m 2 s 21. Diapycnal diffusivity estimated from turbulent kinetic energy dissipation measurements about the area occupied by the tracer in austral summer 2010 was somewhat less, but still within a factor of 2, at (0.75 6 0.07) 3 10 25 m 2 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
104
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(123 citation statements)
references
References 30 publications
8
104
0
Order By: Relevance
“…Applied in the oceanographic context, this result stipulates that the breaking internal waves contribute to the diapycnal scalar mixing by generating turbulence dominated scales of the order of O(k −1 O ). In agreement with the conclusions reached in Ledwell et al [113], the prevailing in the mid-depth oceanic interior values of N and yield the diapycnal diffusivity that appears to be an order of magnitude smaller than what is necessary to maintain the overturning circulation.…”
Section: Discussionsupporting
confidence: 91%
“…Applied in the oceanographic context, this result stipulates that the breaking internal waves contribute to the diapycnal scalar mixing by generating turbulence dominated scales of the order of O(k −1 O ). In agreement with the conclusions reached in Ledwell et al [113], the prevailing in the mid-depth oceanic interior values of N and yield the diapycnal diffusivity that appears to be an order of magnitude smaller than what is necessary to maintain the overturning circulation.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, the first direct measurements of turbulent dissipation and mixing rates in the Southern Ocean were made as part of the DIMES study. Ledwell et al (2010), St. Laurent et al (2012), and Sheen et al (2014) showed that enhanced internal wave fine-structure and turbulence levels were not widespread, but limited to frontal zones where strong bottom currents collide with steep large-amplitude topography.…”
Section: Observationsmentioning
confidence: 99%
“…A description of the US2 study, as well as a discussion of the US2 data, has been previously presented by Ledwell et al (2010) and St. Laurent et al (2012).…”
Section: Us2mentioning
confidence: 99%
“…Morerever, our ocean model employs a constant vertical mixing coefficient. Observations suggest that abyssal mixing varies greatly in space (i.e., Polzin et al 1997) although thermocline values appear uniformly low (Ledwell et al 1993(Ledwell et al , 2011. The dependance of the FWT on mixing is unclear.…”
Section: The Ocean-atmosphere Symmetrymentioning
confidence: 99%